Luxury marketing, sustainability and technology the future of luxury management - Thaichon, Park; Quach, Sara (Routledge, Taylor & Francis Group, 2023)
"Luxury Marketing, Sustainability and Technology explores how new technologies, sustainability and relationship marketing impact and change the future of luxury brand management. Whilst the luxury industry is experiencing exponential growth, further research is vital to improve knowledge and understand how luxury management operates in the new age of marketing. Through a range of empirical and theoretical contributions, this book offers clear insights on relationship marketing and luxury management. It examines the growth of luxury, marketing strategies for luxury brands, advertising and communication of luxury brands, AI and disruptive technology in luxury marketing, and sustainability and pro-environmental luxury. All the chapters close with practical summaries and recommendations for businesses practice. This book is a useful reference for scholars and postgraduate researchers across luxury management and marketing, including those interested in international marketing, social media marketing, fashion management, as well as innovation management and sustainability"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Luxury goods industry -- Management; Retail trade -- Management; Produits de luxe; Industrie; Gestion; Retail trade; Management